The Value of the Buddhist Art as depicted the Khmer Castles in Surin Province - et. al., Thanarat Sa-ard-iam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this article were 1) to present the Buddhist art as depicted in the Khmer castles, to examine the value of Buddhist art as depicted in the Khmer castles. Historical documents and archaeological evidence were used. The result indicated that: When Buddhism was spread into the Suvarnabhumi region during the 3rd century AD, there was a devotee and dedication to create art related to Buddhism. Thus, this art is called Buddhist art. Among all the important civilizations in this world, the Khmer civilization, which is one of the important civilizations in Southeast Asia. The forms of Khmer architecture or Lopburi architecture can be divided into 3 types: (1) Devalai or temple (2) Dhammasala, accommodation for travelers, or houses with lights (3) Arogayasala (Chapel of the hospital). Surin province is located in the northeast of Thailand. There are a large number of Khmer castles. In this province, the castles of Brahmanism and Buddhism had been settled. The Buddhist arts had reflected through architecture. It was indicated that this area used to have Mahayana Buddhism. Although the Buddhist Mahayana sect at present has deteriorated. Historical evidence and values still exist nowadays